Стратегічні пріоритети виходу підприємства на зарубіжні ринки агропромислової продукції - Подварко, Анастасія Дмитрівна; Podvarko, Anastasiia (ЦНТУ, 2021)
В роботі досліджено стратегії виходу аграрних підприємств на зарубіжні ринки. Проаналізовано стан виробництва та реалізації вітчизняної агропродовольчої продукції, визначено пріоритетні напрями її експорту. Окреслено тенденції розвитку зарубіжних ринків агропромислової продукції та визначено частку участі в них України. Досліджено перспективні напрями зовнішньої торгівлі агропромисловою продукцією між Україною і зарубіжними країнами. Запропоновано стратегічні пріоритетні орієнтири для посилення українських позицій на зарубіжних ринках агропромислової продукції. Здійснено оцінку потенціалу аграрного підприємства та обґрунтовано стратегію його виходу на зарубіжні ринки агропромислової продукції. The paper examines the strategies of agricultural enterprises entering foreign markets. The state of production and sale of domestic agri-food products is analyzed, priority directions of its export are determined. Trends in the development of foreign markets for agro-industrial products are outlined and the share of Ukraine's participation is determined. Promising directions of foreign trade in agro-industrial products between Ukraine and foreign countries are studied. Strategic priority guidelines for strengthening Ukraine's position in foreign markets of agro-industrial products are proposed. The potential of the agricultural enterprise was assessed and the strategy of its entry into foreign markets of agro-industrial products was defined.
Strategic Priorities of the Company's Entering Foreign Markets of Agricultural Products
Keywords: стратегія; аграрні підприємства; пріоритетні напрями; експорт агропродовольчої продукції; strategy; agicultural enterprises; priority directions; export of agro-food products